Dental stem cell-derived extracellular vesicles as promising therapeutic agents in the treatment of diseases - Li, Ye; Duan, Xu; Chen, Yinxue; Liu, Bingyun; Chen, Gang (International journal of oral science, 2022)
Dental stem cells (DSCs), an important source of mesenchymal stem cells (MSCs), can be easily obtained by minimally invasive procedures and have been used for the treatment of various diseases. Classic paradigm attributed the mechanism of their therapeutic action to direct cell differentiation after targeted migration, while contemporary insights into indirect paracrine effect opened new avenues for the mystery of their actual low engraftment and differentiation ability in vivo. As critical paracrine effectors, DSC-derived extracellular vesicles (DSC-EVs) are being increasingly linked to the positive effects of DSCs by an evolving body of in vivo studies. Carrying bioactive contents and presenting therapeutic potential in certain diseases, DSC-EVs have been introduced as promising treatments. Here, we systematically review the latest in vivo evidence that supports the therapeutic effects of DSC-EVs with mechanistic studies. In addition, current challenges and future directions for the clinical translation of DSC-EVs are also highlighted to call for more attentions to the (I) distinguishing features of DSC-EVs compared with other types of MSC-EVs, (II) heterogeneity among different subtypes of DSC-derived EVs, (III) action modes of DSC-EVs, (IV) standardization for eligible DSC-EVs and (V) safety guarantee for the clinical application of DSC-EVs. The present review would provide valuable insights into the emerging opportunities of DSC-EVs in future clinical applications.